Association of N6-methyladenosine readers' genes variation and expression level with pulmonary tuberculosis - Li, Hong-Miao; Tang, Fei; Wang, Li-Jun; Huang, Qian; Pan, Hai-Feng; Zhang, Tian-Ping (Frontiers in Public Health, 2022)
N6-methyladenosine (m6A) is associated with many biological processes and the development of multiple diseases. Our study aimed to analyze the association of m6A readers’ genes variation, as well as their expression levels, with pulmonary tuberculosis (PTB). Eleven single nucleotide polymorphisms (SNPs) in m6A readers’ genes (YTHDF1 rs6122103, rs6011668, YTHDF2 rs602345, rs3738067, YTHDF3 rs7464, rs12549833, YTHDC1 rs3813832, rs17592288, rs2293596, and YTHDC2 rs6594732, rs2416282) were genotyped by iMLDR in 457 PTB patients and 466 normal controls. The m6A readers’ genes expression levels in peripheral blood mononuclear cells (PBMCs) from 78 PTB patients and 86 normal controls were detected by qRT-PCR. There was no significant association between all SNPs in YTHDF1, YTHDF2, YTHDF3, YTHDC1, YTHDC2 genes and PTB susceptibility. The increased frequencies of YTHDF2 rs3738067 GG genotype and YTHDC1 rs3813832 CC genotype, C allele were respectively found in the PTB patients with hypoproteinemia and fever. YTHDC2 rs6594732 variant was significantly associated with drug-induced liver damage, sputum smear-positive, and rs2416282 variant was significantly in relation with fever in PTB patients. Compared with controls, the YTHDF1, YTHDF2, YTHDF3, YTHDC1 and YTHDC2 mRNA levels were significantly decreased in PTB. Moreover, YTHDF1 level was negatively associated with ESR and YTHDF3, YTHDC1 levels were negatively related to ALT in PTB patients. Our results demonstrated that YTHDF1, YTHDF2, YTHDF3, YTHDC1 and YTHDC2 genes SNPs were not contribute to PTB susceptibility, while their decreased levels in PTB patients suggested that these m6A readers might play significant roles in PTB.